Chronotopic Cartography: Mapping Literary Time-Space. (20th April 2021) - Bushell, Sally; Butler, James; Hay, Duncan; Hutcheon, Rebecca; Butterworth, Alex
Abstract: This short methods paper emerges out of the AHRC-funded 'Chronotopic Cartographies' project for the digital mapping of place and space as represented in works of literature. The primary aim of that project was to find a way of mapping and visualizing represented literary worlds for which there is no corresponding real 'ground'. A solution was found in the form of topological graphs which allow for relative rather than absolute mapping (but also permit a relative imaginary map to be lain on top of a pre-existing cartesian form). Using a spatial schema to chunk out the text in terms of chronotopic (time-space) zones enables the generation of a series of visualizations that show different kinds of spatio-temporal constructions in texts. The visualizations are centred upon nodes that consist of chronotopes (e.g. 'the road') as well as locations (e.g. 'road to Geneva'); connections between them of different kinds and toporefs within them (references to other places from this one). The paper will articulate core methods from the project, outlining the stages involved in the process, from marking up the text, using a custom-made schema, through graph generation and into the implications for analysis. This will be illustrated in relation to two Victorian texts: the realist space of Dickens's Oliver Twist ; and the abstract poetic space of Browning's 'Childe Roland to the Dark Tower Came'.